Prenatal Diagnosis and Management of Advanced Abdominal Pregnancy in Dr. Moewardi Hospital Surakarta: A Case Series - Akbar, Uchti; Anggraini, Nutria Widya Purna; Yuliantara, Eric Edwin; Bachnas, Muhammad Adrianes; Ridwan, Robert; Sulistyowati, Sri (Journal of Maternal and Child Health, 2021)
Background: The abdominal pregnancy is a pregnancy anywhere in the abdominal cavity other than the tube, ovary, and broad ligament. Abdominal pregnancy has 7.7 times greater risk than tubal pregnancy and 90 times greater than intrauterine pregnancy. This study aims to reveal the diagnosis and treatment of abdominal pregnancy in Dr. Moewardi Hospital Surakarta. Subjects and Method: This was a case series study conducted at Dr. Moewardi Hospital Surakarta. This study report three cases of advanced abdominal pregnancy at Dr Moewardi Hospital (2019 – 2020), that consisted of two cases of advanced abdominal pregnancy to term, and one advanced abdominal pregnancy with acute abdomen. Case presentation: Case 1 (it was found abdominal pregnancy at 30 weeks), the condition of the mother and the fetus was good, the pregnancy was continued until the gestational age was term. The patient was given corticosteroids for lung maturation and magnesium sulfate for neuroprotection. Case 2 (an abdominal pregnancy was found at term), it was decided to immediately terminate it with good preoperative preparation. Both patients in case 1 and case 2 had good result in both the mother and the fetus. The placenta was left in situ in both cases to prevent massive bleeding and injury to the gastrointestinal organs. Case 3 (advanced abdominal pregnancy with acute abdominal symptoms) decided to undergo an emergency laparotomy and removal of the placenta. Conclusion: Abdominal pregnancy must be diagnosed and managed properly to reduce maternal mortality and morbidity. In advanced abdominal pregnancy, it could be considered to continue the pregnancy until the term. The placenta management of in situ without methotrexate might be considered in cases of abdominal pregnancy.